Damage of 3D tungsten targets in the course of ITER ELM-like heat loads - Herashchenko, S.S.; Makhlaj, V.A.; Aksenov, N.N.; Byrka, O.V.; Chebotarev, V.V.; Kulik, N.V.; Lebedev, S.I.; Shevchuk, P.B.; Staltsov, V.V. (Вопросы атомной науки и техники, 2017)
The damage of tungsten target under repetitive plasma loads have been studied with a quasi-stationary plasma accelerator QSPA Kh-50. The target construction was close to the ITER divertor reference design. The plasma stream parameters were relevant to ITER ELMs (surface heat load of 0.9 MJ/m² and pulse duration of 0.25 ms). The features of surface erosion and particle emission have been investigated in the course of increasing number of plasma pulses. The number of solid/droplet particles separated from the exposed target and their dynamics depend on the applied exposition dose. The contribution of different erosion mechanisms to the tungsten target destruction was evaluated.